경기육괴 남동부 (원주-영월-횡성 지역) 전기 페름기에서 후기 트라이아스기의 변성작용: 한반도 중부의 페름기-트라이아스기 지구조진화사 대한 시사점 - 이병춘; 오창환; Byung Choon Lee; Chang Whan Oh (자원환경지질, 2024)
In this study, we conducted metamorphic P-T estimation and zircon U-Pb age dating for the Chiaksan gneiss in the Wonju-Yeongwol-Hoengseong area in the southeastern Gyeonggi Massif to examine Permian-Triassic metamorphic events occurred in the region. The results of metamorphic P-T estimation using conventional geothermobarometer and pseudosection analysis show that the Chiaksan gneiss underwent intermediate-P/T (656-696℃/8.3-8.7 Kbar) and low-P/T (756-759℃/6.3-6.9 Kbar) metamorphism during prograde and peak metamorphic stages, respectively. After the peak metamorphism, the Chiaksan gneiss experienced retrograde metamorphism (567-612℃/2.2-2.8 Kbar). By combining the results of metamorphic P-T estimation with mineral paragenesis and texture, it was confirmed that successive metamorphic events, from prograde to retrograde metamorphism, occurred along a clockwise P-T path. Additionally, it was identified that partial melting of Chiaksan gneiss occurred due to the dehydration reaction of muscovite during prograde to peak metamorphism. From zircon U-Pb age analysis, metamorphic ages corresponding to the Paleoproterozoic era (1923 Ma) and Permian-Triassic (278 Ma, 229.9 Ma) are recognized in the Chiaksan gneiss, and the peak and retrograde metamorphism of the Chiaksan gneiss were confirmed to have occurred at 278 Ma and 229 Ma, respectively. Considering the metamorphic geothermal gradient identified in this study and the results of previous studies, the regional metamorphism related to the orogenic event occurred in the southeastern Gyeonggi Massif during the Permian-Triassic period. This metamorphic event occurred in an arc-related tectonic setting that was developed in the southeastern part of the Korean Peninsula at that time. 경기육괴 남동부 원주시-영월군-횡성군 일대에 분포하는 선캠브리아 시대 치악산편마암의 변성 온도-압력 계산 및 저어콘 U-Pb 연대측정을 바탕으로 경기육괴 남동부에서 발생한 페름기-트라이아스기 변성작용에 대한 연구를 수행했다. 지온-지압계와 가단면 분석 결과에 따르면 연구지역에 분포하는 치악산편마암은 656-696℃/8.3-8.7 Kbar에 해당하는 중압형 전진 변성작용을 경험한 뒤 756-759℃/6.3-6.9 Kbar의 저압형(백림암상) 정점 변성작용을 경험했으며, 이후 567-612℃/2.2-2.8 Kbar에 해당하는 후퇴 변성작용을 경험한 것으로 나타난다. 변성광물의 공생관계와 조직을 고려해 볼 때 연구지역에서 인지되는 변성작용은 시계방향의 경로를 따라 발생한 것으로 확인되었으며, 전진 변성작용에서 정점 변성작용이 일어나는 동안 백운모의 탈수반응에 의해 부분용융 작용이 발생한 것으로 확인되었다. 저어콘 U-Pb 연대측정 결과에 의하면 치악산편마암에서는 고원생대(1923 Ma)와 페름기-트라이아스기 (278 Ma, 229.9 Ma)에 해당하는 변성연령이 인지되며, 치악산편마암의 정점 변성작용시기와 후퇴 변성작용시기는 각각 278 Ma와 229.9 Ma에 발생한 것으로 확인되었다. 본연구에서 확인된 변성작용의 지온구배와 기존연구 결과를 고려해보면 페름기-트라이아스기에 경기육괴 남동부에서는 조산운동과 관련된 광역 변성작용이 발생했으며 이들 변성작용은 당시 한반도 남동부에 발달 되어있던 화산호 환경하에서 발생했던 것으로 판단된다.